Variation of the optical properties of soot as a function of particle mass. (November 2017) - Dastanpour, Ramin; Momenimovahed, Ali; Thomson, Kevin; Olfert, Jason; Rogak, Steven
Abstract: Light absorption and scattering properties of combustion-generated soot particles are important to measurement methods and are used as the inputs for climate models. For decades, mass-specific absorption cross section (MAC) of soot has been assumed to be independent of its size and mass. Here we investigate the size-dependent optical properties of particles produced by a single source. Soot particles were produced by combustion of CH4, and CH4 - N2 mixtures, within a laminar inverted diffusion flame. Extinction and scattering coefficients of mass-classified particles were measured by a Cavity Attenuated Phase Shift Single Scattering Albedo Spectrometer. Primary particle diameter and morphology of particles were characterized by transmission electron microscopy. Graphitization level of the size-classified particles was also investigated by Raman spectroscopy. Here, for the first time we observed that MAC and graphitization level of the soot particles increase with the particle mass. MAC number increases from approximately 4.5 to 8.5 (m 2 g −1 ) with the particle mass increasing from 0.05 fg to 8 fg. The soot aggregate size is correlated with primary particle size, which may reflect the inhomogeneity of the combustion environment that could affect the optical properties of soot. Graphical abstract: